2018
DOI: 10.18203/2320-6012.ijrms20180592
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of thyroid dysfunctions among Nigerian patients with vitiligo

Abstract: Background: Vitiligo is associated with varying degrees of thyroid dysfunctions. This study was aimed to evaluate the thyroid dysfunctions in patients with vitiligo in Port Harcourt, Nigeria, West Africa.Methods: A retrospective, descriptive, cross-sectional analysis of thyroid function tests variables of 105 vitiligo patients who visited the Department of Chemical Pathology and Metabolic Medicine of the University of Port Harcourt Teaching Hospital between 1st January 2012 and 31st December 2016 was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Some studies have shown that vitiligo in patients with autoimmune thyroid disease is mainly non-segmental, and in the segmental type is rare. [14][15] In this study, the incidence of non-segmental vitiligo was high in the adults (322/370[87.0%]) and advanced age (25/26[96.2%]) with a high incidence of thyroid dysfunction. Similar to our results, hypertension and diabetes mellitus have also been reported as underlying associated diseases among patients with vitiligo in a previous study.…”
Section: Discussionmentioning
confidence: 69%
“…Some studies have shown that vitiligo in patients with autoimmune thyroid disease is mainly non-segmental, and in the segmental type is rare. [14][15] In this study, the incidence of non-segmental vitiligo was high in the adults (322/370[87.0%]) and advanced age (25/26[96.2%]) with a high incidence of thyroid dysfunction. Similar to our results, hypertension and diabetes mellitus have also been reported as underlying associated diseases among patients with vitiligo in a previous study.…”
Section: Discussionmentioning
confidence: 69%